Aflatoxin B1 Promotes Influenza Replication and Increases Virus Related Lung Damage via Activation of TLR4 Signaling - Sun, Yuhang; Su, Jiarui; Liu, Zixuan; Liu, Dandan; Gan, Fang; Chen, Xingxiang; Huang, Kehe (Frontiers in Immunology, 2018)
Aflatoxin B1 (AFB1), which alters immune responses to mammals, is one of the most common mycotoxins in feeds and food. Swine influenza virus (SIV) is a major pathogen of both animals and humans. However, there have been few studies about the relationship between AFB1 exposure and SIV replication. Here, for the first time, we investigated the involvement of AFB1 in SIV replication in vitro and in vivo and explored the underlying mechanism using multiple cell lines and mouse models. In vitro studies demonstrated that low concentrations of AFB1 (0.01–0.25 μg/ml) markedly promoted SIV replication as revealed by increased viral titers and matrix protein (M) mRNA and nucleoprotein (NP) levels in MDCK cells, A549 cells and PAMs. In vivo studies showed that 10–40 μg/kg of AFB1 exacerbated SIV infection in mice as illustrated by significantly higher lung virus titers, viral M mRNA levels, NP levels, lung indexes and more severe lung damage. Further study showed that AFB1 upregulated TLR4, but not other TLRs, in SIV-infected PAMs. Moreover, AFB1 activated TLR4 signaling as demonstrated by the increases of phosphorylated NFκB p65 and TNF-α release in PAMs and mice. In contrast, TLR4 knockdown or the use of BAY 11-7082, a specific inhibitor of NFκB, blocked the AFB1-promoted SIV replication and inflammatory responses in PAMs. Furthermore, a TLR4-specific antagonist, TAK242, and TLR4 knockout both attenuated the AFB1-promoted SIV replication, inflammation and lung damage in mice. We therefore conclude that AFB1 exposure aggravates SIV replication, inflammation and lung damage by activating TLR4-NFκB signaling.